Marfim, in natura e lavrado, no Inventarium Maragnonense (1760) com ênfase na representação do Cristo crucificado - Isis de Melo Molinari Antunes (2020)
This thesis studies the use of ivories, in natura and wrought, which were identified in the Inventarium Maragnonense – Inventory of the Churches and Jesuit Chapels in the State of Maranhão and Grão-Pará in the year 1760, which got dissociated along the years. The study of the crucified Christ representation was selected because it is the most frequent shape mentioned in the inventory, and secondarily, other religious forms were considered, besides ivory tusks, ivory pieces and ivory dust. The main hypothesis of this work is to prove that even in the absence of those objects, it is possible to conceive methods to maintain the memory of the cultural and material patrimony, through the investigation of the routes taken by those objects, and with the assistance of documental imagery and historical sources, which complement each other. This work used bibliograhy with support from several fields: History of Art, History and Iconography. For the study of the Crucified iconography an exhaustive in loco investigation was performed in the National Historic Museum in Rio de Janeiro, using photographic records of 74 images of the Christ in the cross, at several positions with their respective measurements.The main goal of this thesis was to ponder about the losses and conserved pieces of the ivory collection described in the Inventarium maragnonense. As secondary objectives, we seeked to explain the Crucified Christ iconography by the paintings and drawings (essentially narratives) who helped to propagate the subject matter; to explain the different formal and iconographic characteristics of the Crucified in ivory from different schools of sculpture; to weigh in on the sculpture's assigned nomenclatures; to study the iconographic programs adopted by the Jesuit Churches, and more specifically, in the Church of São Francisco Xavier, in Belém, Pará; to investigate the presence of in natura ivory in the chemist's shops of the Jesuitic Schools of the old North States;to investigate the ingress of ivory raw material in Maranhão and Grão-Pará; to identify the possible routes for transportation of that material, its ties with slave trade and the point of ingress of the raw material; and finally, to find out the reasons for the dissociation of the sacred ivory images, which belonged to the Society of Jesus. New nomenclatures were created as contributions from this thesis, from europeans, asians and sui generis, to designate a style associated to the manufacture origin, following the vernacular tradition, in substitution of the nomenclature normally used by the Indo-Portuguese, Sino-Portuguese, Cingalo-Portuguese and Spanish-Philippine languages. As a means to memory rescue, we built a hypothetical reconstruction of the sacred spaces of the Church of São Francisco Xavier, by the proper positioning of the colonial images and ornaments in the places indicated by the Inventarium. And finally, we highlighted the existence of two ivory images, remaining intact until the present time.